Journalists’ algorithmic literacy: Attitudes towards social media and generative AI - Couraceiro, P.; Foá, C.; Pinto-Martinho, A. (ESSACHESS - Journal for Communication Studies, 2025)
This study explores the relationship between Portuguese journalists’ satisfaction with the adoption of digital tools and their algorithmic literacy across cognitive, affective, and behavioral dimensions. Based on an online survey (N = 219) and three focus groups, our findings indicate that a greater proportion of journalists who are overall satisfied with digital tools for their work recognizes the benefits of social media and generative AI, while still acknowledging associated risks. They also declare higher self-perceived competence, yet proficiency in generative AI remains notably low. Additionally, socio-professional differences emerge, with younger journalists and those working in online outlets or local/regional media expressing greater overall satisfaction with digital tools. The findings highlight that individual motivation and organizational context jointly shape algorithmic literacy, underscoring the need for targeted algorithmic literacy initiatives in journalism.